2019
DOI: 10.1108/jarhe-07-2018-0115
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of identity strength and organizational citizenship behavior (OCB) in establishing good university governance and performance of religious ideology-based higher educations

Abstract: Purpose The purpose of this paper is to determine the effect of identity strength and organizational citizenship behavior (OCB) on good university governance and its impact on performance of religious ideology-based universities. Design/methodology/approach The design of this study was an explanatory design. This study had a deductive theoretical direction; therefore, the core method was quantitative. The “import” strategy served as a complement to the main method. With the time horizon, the selection of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
(8 reference statements)
1
23
0
1
Order By: Relevance
“…The results of the study of Rymarzak et al (2019) show that the existence of university governance reforms must take into account the resources and facilities, if ignoring this will cause the university to be less than optimal and consequently affect the university's accountability, productivity, performance and competitive advantage. According to Munawir et al (2019), accountability must be fulfilled by public JIAFR | 46 sector organizations, one of which is accountability for honesty related to avoiding abuse of authority and power. The Financial and Development Supervisory Agency (BPKP) emphasizes the importance of accountability that considers moral and ethical issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study of Rymarzak et al (2019) show that the existence of university governance reforms must take into account the resources and facilities, if ignoring this will cause the university to be less than optimal and consequently affect the university's accountability, productivity, performance and competitive advantage. According to Munawir et al (2019), accountability must be fulfilled by public JIAFR | 46 sector organizations, one of which is accountability for honesty related to avoiding abuse of authority and power. The Financial and Development Supervisory Agency (BPKP) emphasizes the importance of accountability that considers moral and ethical issues.…”
Section: Resultsmentioning
confidence: 99%
“…Simply put, a good university can be seen as the application of the basic principles of "good governance" concepts in the system and process of governance in higher education institutions, through various adjustments made based on values that must be upheld in the administration of higher education. This is based on the aim of developing academic and scientific education and developing whole people (Munawir et al, 2019).…”
Section: Good University Governancementioning
confidence: 99%
“…Subsequently, evidence also revealed that good university management and performance would also succeed as the OCB succeeds. Thus, good university governance strengthens the relationship between OCB and university performance (Munawir et al, 2019).…”
Section: Overview Of Organizational Citizenship Behavior (Ocb) Practices In Higher Educationmentioning
confidence: 98%
“…Such behaviors are designated clearly in the construct of OCB in organization (Zareiematin, Alvani, Jandaghi, & Ahmadi, 2010). Likewise, OCB has made a positive contribution to the development of organizations, such as to improve the quality of service (Koning & Kleef, 2015), organizational engagement (Carpenter, Berry, & Houston, 2014), increase good university government (Munawir, Raharjo, Djalil, Syahputra, Muslim, & Adam, 2019), job satisfaction and organizational commitment of Higher Education (Romi & Ahman, 2020). Some have also suggested that OCB is likely to produce higher organizational performance and efficiency when aggregated over time and across individuals (Takeuchi, Bolino, & Lin, 2015;Shin, Kim, Choi, & Oh, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation